Experimental study of three commercially available 18650 lithium ion batteries using multiple abuse methods. (15th August 2023) - Abbott, Katie C.; Buston, Jonathan E.H.; Gill, Jason; Goddard, Steven L.; Howard, Daniel; Howard, Gemma E.; Read, Elliott; Williams, Rhiannon C.E.
Abstract: This study provides a comparative analysis of three commercially available and electrically similar lithium-ion batteries with a nominal capacity of 3 Ah, through a series of thermal, electrical, and mechanical abuse. Swab samples suggested that one cell type had an NMC [Li(Nix Mny Co1-x-y )O2 ]cathode, and the remaining two had an NCA [Li(Nix Coy Al1-x-y )O2 ]cathode. The precise nature of the chemical compositions and their ratios are not known. Repeated ARC tests showed that the three cells had comparable self-heating temperatures (~83 °C). Downward pressures of up to 41.5 kPa were recorded but were varied across all cells, and the furthest distance it travelled was over 40 m. Pressure vessel tests indicated that at least 20 L of air is required to ensure complete combustion, and higher molar concentrations in a nitrogen environment were witnessed for the NCA cells compared to the NMC cell, ~0.067 and ~0.052 mol Ah −1, respectively. Overcharge tests at higher charging rates approached temperatures required for thermal runaway, and a variety of safety mechanisms were observed. Comparable LIBs on paper do not always fail in the same way and therefore the results from one test cannot be reliably extrapolated to different cells despite their similarities. Graphical abstract: Unlabelled Image Highlights: 3 Different, but comparable, 3 Ah 18, 650 cells evaluated Multiple abuse methods employed Different failure outcomes observed between the cells Gas volume and composition measured